ADVANCES IN AUTOMOBILE SUSPENSION SYSTEM - Siddhant Halnor (International Journal of Innovations in Engineering Research and Technology, 2021)
This study reviews the initial development of suspension system, necessity of suspension system for an automobile sector, concept of vibration, its causes, reasons and effects of vibrations on the automobile system. This review also includes important information on advanced suspension systems for automobiles, conventional and non-conventional suspension systems, a brief information about conventional suspension systems containing springs, shock absorbers, and dampers. A brief introduction of some of the recent suspension systems used in the automobiles today is also elaborated like Bose suspension system which includes the use of the linear electromagnetic motor, double wishbone suspension system, Ferro-fluid or magneto-rheological dampers and Ford’s control blade suspension system. These suspension systems are now-a-days being included in to various automobiles to reduce the overall body motion and jarring vibrations and enhance comfort and control.